Liability of the supervisor under petroleum drilling contract; IOP Conference Series: Earth and Environmental Science; Vol. 24 : Scientific and Technical Challenges in the Well Drilling Progress, 24–27 November 2014, Tomsk, Russia - Sizov A. V. Aleksey Valentinovich; Tretyakov K. N. Konstantin Nikolaevich; Boyarko G. Yu. Grigory Yurievich; Shenderova I. V. Inna Vladimirovna (2015, 2015)
Title screen